Can the Use of Variable-Angle Volar Locking Plates Compensate for Suboptimal Plate Positioning in Unstable Distal Radius Fractures? A Biomechanical Study. Issue 1 (January 2015) - Hart, Adam; Collins, Melissa; Chhatwal, Dane; Steffen, Thomas; Harvey, Edward J.; Martineau, Paul A.
Abstract : Objective: To compare the biomechanical stability under load-to-failure conditions of optimally placed fixed-angle volar locking plates versus suboptimally placed variable-angle volar locking plates in unstable, intraarticular distal radius fractures. Methods: A Melone type 1 (AO 23-C3) fracture was created in 25 sawbone radii and plated with either a fixed-angle or variable-angle Synthes plate with identical profile. Four plate positions were tested: distal ulnar (DU, positioned distally to obtain subchondral support and ulnar to hold the lunate facet fragments), distal radial (DR, 3 mm radial to DU), proximal ulnar (PU, 3 mm proximal to DU), and proximal radial (PR, 3 mm proximal and 3 mm radial to DU). The specimens were loaded until failure as defined by a 2-mm displacement of any fracture fragment. The fixed-angle plates were tested in the DU position, whereas the variable-angle plates were tested in all 4 positions. Results: The dorsal lunate fragment was the first to fail in every group followed by the radial styloid and volar lunate fragments, respectively. Load-to-failure, from greatest to least, occurred at the DR (278 ± 56 N), PR (277 ± 68 N), DU fixed-angle (277 ± 68 N), DU variable-angle (236 ± 31 N), and PU (202 ± 75 N) positions, respectively. Rigidity was calculated using the slope of the dorsal lunate force–displacement curve before failure (at loads 100–150 N). Rigidity was greatest at the PU position (126 ± 60 N/mm) followed by PR (125 ± 30 N/mm), DU fixed-angle (125 ± 25 N/mm), DR (122 ± 66 N/mm), and DU variable-angle (101 ± 35) positions, respectively. Univariate analysis of rigidity and load-to-failure was not significantly different between groups. Conclusions: In this experimental model, variable-angle screws provided a leeway of 3 mm in both the sagittal and coronal directions without sacrificing construct strength, which may considerably facilitate fixation of these difficult fractures.